Effects of testosterone on orchiectomy-induced oxidative damage in the rat hippocampus - Meydan, Sedat; Kus, Ilter; Tas, Ufuk; Ogeturk, Murat; Sancakdar, Enver; Dabak, Durrin Ozlem; Sarsilmaz, Mustafa (Elsevier, 2010)
The aim of this study was to investigate the morphological changes of the hippocampus after orchiectomy and the protective effects of testosterone on these changes. Animals were divided into 3 groups. The rats in group I were used for sham-orchiectomy. Orchiectomy was performed on the rats in group II. The rats in group III were administrated testosterone propionate 0.5 mg/kg/day for 30 days after the orchiectomy. Some of the hippocampal tissues were used for determination of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) enzyme activities, and malondialdehyde (MDA) levels. The remaining hippocampal tissue specimens were stained with routine histological methods and examined under the light microscope. Additionally, the samples were immunohistochemically stained by using avidin-biotin-peroxidase for determination of bax immunoreactivity. The SOD and GSH-Px enzyme activities of the hippocampus were decreased, and MDA levels were increased in group II rats compared to the sham-orchiectomy group. In the light microscopic evaluation of the tissue specimens from group II, significant increases were detected in the number of picnotic cells and in bax immunoreactivity compared to the sham-orchiectomy group. However, an increase was observed in activities of SOD and GSH-Px enzymes and a decrease of the MDA levels in animals with orchiectomy, but having externally administered testosterone. It was determined that the increase of bax immunoreactivity and histopathological changes in this group were regressed by testosterone. The results of our study revealed that orchiectomy-induced oxidative damage and morphological changes in the hippocampal tissue were suppressed by testosterone. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hippocampus; Testosterone; Orchiectomy; Immunohistochemistly; Rat